The Cultural and Contextual Adaptation Process of an Intervention to Reduce Psychological Distress in Young Adolescents Living in Lebanon - Brown, Felicity L.; Aoun, May; Taha, Karine; Steen, Frederik; Hansen, Pernille; Bird, Martha; Dawson, Katie S.; Watts, Sarah; Chammay, Rabih el; Sijbrandij, Marit; Malik, Aiysha; Jordans, Mark J. D. (Frontiers in Psychiatry, 2020)
Armed conflict leads to increased risk of emotional distress amongst children and adolescents, and increased exposure to significant daily stressors such as poverty and community and family violence. Unfortunately, these increased risks usually occur in the context of largely unavailable mental health services. There is growing empirical support that evidence-based treatment techniques can be adapted and delivered by non-specialists with high fidelity and effectiveness. However, in order to improve feasibility, applicability, and outcomes, appropriate cultural and contextual adaptation is essential when delivering in different settings and cultures. This paper reports the adaptation process conducted on a new World Health Organization psychological intervention- Early Adolescent Skills for Emotions (EASE) – for use in the north of Lebanon. Lebanon is a middle-income country that hosts the largest number of refugees per capita globally. We conducted: i) a scoping review of literature on mental health in Lebanon, with a focus on Syrian refugees; ii) a rapid qualitative assessment with adolescents, caregivers, community members, and health professionals; iii) cognitive interviews regarding the applicability of EASE materials; iv) a psychologist review to reach optimal and consistent Arabic translation of key terms; v) ‘mock sessions’ of the intervention with field staff and clinical psychology experts; vi) gathering feedback from the Training of Trainers workshop, and subsequent implementation of practice sessions; and vii) gathering feedback from the Training of Facilitators workshop, and from attendance data from subsequent implementation of practice sessions. Several changes were implemented to the materials- some were Lebanon-specific cultural adaptations, while others were incorporated into original materials as they were considered relevant for all contexts of adversity. Overall, our experience with adaptation of the EASE programme in Lebanon is promising and indicates the acceptability and feasibility of a brief, non-specialist delivered intervention for adolescents and caregivers. The study informs the wider field of global mental health in terms of opportunities and challenges of adapting and implementing low-intensity psychological interventions in settings of low resources and high adversity.